Расселение крымскотатарского населения до депортации на территории Крыма - Меметова, Р.Ш. (Культура народов Причерноморья, 2013)
Проаналізовано історію заселення, чисельність й географія місць компактного проживання
кримськотатарського населення на території Криму до депортації й після неї. Вивчено динаміку
чисельності кримських татар на території Криму з 18 й до 20 століть.
Ключові слова: розселення, кримські татари. Проанализирована история заселения, численность и география мест компактного
проживания крымскотатарского населения на территории Крыма до депортации и после нее. Изучена
динамика численности крымских татар с 18 и до 20 веков.
Ключевые слова:расселение, крымские татары. The article is devoted to analysis of the history of settlement, of the population and the geography of
the places of compact residing of the Crimean Tatar population in Crimea before and after the deportation, as
well as to the research the dynamics of the population of Crimean Tatars from the 18 till 20 centuries.During
this period, the population and ethnic structure of the Crimea were changed due to the different historical
processes. The Crimean Tatars – is the ethnos, was formed in the Crimea as a result of a complex process of the
ethnic consolidation, assimilation, separation of individual religious groups. In the 18th century as a result of the
resettlement of the Greeks and Armenians to the territory of the Russian Empire population and the ethnic
structure in the Crimea were changed, considerably increased the share of the Crimean Tatar population. But
from the end of 18th century there was sustainable tendency to reduce Crimean Tatar population in Crimea, the
part of the Crimean Tatar people left Crimea and emigrated to Turkey, that was associated with the annexation
of Crimea to Russia. The information presented in the article showed that the largest number of the Crimean
Tatar population was concentrated in the foothills and the southern coast of the Crimean Peninsula, majority
lived in rural areas (in southern coast), and the least – in the plains.
Key words:settlement, the Crimean Tatars.